2013
DOI: 10.1111/j.1365-2702.2012.04321.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive patients' experience with adherence therapy for enhancing medication compliance: a qualitative exploration

Abstract: Exploring patients' experience with AT and recognising these five elements help in tailoring a new effective strategy according to individual needs for enhancing adherence to prescribed drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 43 publications
3
23
0
1
Order By: Relevance
“…Physicians' communication with patients with hypertension and clear instructions on antihypertensive medication were anticipated to affect patient's adherence positively. There was also a positive impact of the education and counselling (offered by health-care professionals) on patients' adherence to their antihypertensive medication as indicated in similar studies (41,42). The frequency of medication changes by the physician affected our patients' adherence in a negative fashion, as reported in another study (43).…”
Section: Discussionsupporting
confidence: 57%
“…Physicians' communication with patients with hypertension and clear instructions on antihypertensive medication were anticipated to affect patient's adherence positively. There was also a positive impact of the education and counselling (offered by health-care professionals) on patients' adherence to their antihypertensive medication as indicated in similar studies (41,42). The frequency of medication changes by the physician affected our patients' adherence in a negative fashion, as reported in another study (43).…”
Section: Discussionsupporting
confidence: 57%
“…, Alhalaiqa et al . ). However, the findings are relatively inconsistent (Hagger & Orbell , Victor et al .…”
Section: Introductionmentioning
confidence: 97%
“…Studies have suggested the usefulness of exploring adherence from the patient perspective (Chen et al 2009, Alhalaiqa et al 2013). However, the findings are relatively inconsistent (Hagger & Orbell 2003, Victor et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Medication non-compliance contributes to low rates of HTN control but does not account for all the variability seen in response to blood pressure drugs. Despite numerous strategies to improve compliance [58], drug effectiveness [9, 10], and optimization of initial drug choice [4], effectiveness has remained largely unchanged over the past two decades [11]. …”
Section: Introductionmentioning
confidence: 99%